2022
DOI: 10.1096/fj.202200005rr
|View full text |Cite
|
Sign up to set email alerts
|

RNA demethylase ALKBH5 inhibits TGF‐β‐induced EMT by regulating TGF‐β/SMAD signaling in non‐small cell lung cancer

Abstract: AlkB homolog 5 (ALKBH5) has been revealed as a key RNA N6‐methyladenosine (m6A) demethylase that is implicated in development and diseases. However, the function of ALKBH5 in TGF‐β‐induced epithelial‐mesenchymal transition (EMT) and tumor metastasis of non‐small‐cell lung cancer (NSCLC) remains unknown. Here, we firstly show that ALKBH5 expression is significantly reduced in metastatic NSCLC. ALKBH5 overexpression inhibits TGF‐β‐induced EMT and invasion of NSCLC cells, whereas ALKBH5 knockdown promotes the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Gao et al demonstrated that LINC00337 is positively regulated by sponging YTHDF1, with the subsequent promotion of LUAD progression [ 60 ]. Zhang et al found that YTHDF1-mediated TGFβR2 mRNA stabilization and increased expression promote the EMT of NSCLC [ 84 ]. It has been shown that YTHDF1 is up-regulated in 5-fluorouracil (5-FU) and oxaliplatin-resistant NSCLC cells whereas knockdown of YTHDF1 boosts the cisplatin resistance of NSCLC via modulates the Keap1-Nrf2-AKR1C1 axis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al demonstrated that LINC00337 is positively regulated by sponging YTHDF1, with the subsequent promotion of LUAD progression [ 60 ]. Zhang et al found that YTHDF1-mediated TGFβR2 mRNA stabilization and increased expression promote the EMT of NSCLC [ 84 ]. It has been shown that YTHDF1 is up-regulated in 5-fluorouracil (5-FU) and oxaliplatin-resistant NSCLC cells whereas knockdown of YTHDF1 boosts the cisplatin resistance of NSCLC via modulates the Keap1-Nrf2-AKR1C1 axis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…METTL3-mediated m 6 A modification regulates the expression of some osteogenic markers and other related genes involved in bone metabolism [32]. Parathyroid hormone (PTH)/ Pth1r, TGF-β/SMAD, WNT and other signaling pathways are modulated by m 6 A marks, which are essential in the cellular differentiation and cancer development [16,33,34]. Here, NOG and downstream Smad pathway were identified as the target of METTL3-mediated m 6 A modification during DPSC differentiation.…”
Section: Discussionmentioning
confidence: 95%
“…lncRNA AC098934 enhanced the invasion of lung adenocarcinoma cells through METTL3-mediated m 6 A modification in AC098934 [31]. ALKBH5 inhibited TGF-β/SMAD signaling and suppressed TGF-β-induced epithelial-mesenchymal transition (EMT) through reducing m 6 A modifications in NSCLC cells [32]. However, whether m 6 A modification is responsible for the CAFs' effect on lung cancer metastasis has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%